Research: Does the Addition of Ultrasound Enhance Cardiac Anatomy Learning in Undergraduate Medical Education? - Joshua Durbin; Amer M. Johri; Anthony Sanfilippo (POCUS Journal, 2017)
With the advent of portable hand-held ultrasound units, the use of point of care ultrasound (POCUS) has become increasingly popular amongst a wide array of medical specialists for both diagnostic and therapeutic interventions. Canada-wide surveys demonstrate a desire for increased utilization of POCUS in primary medical education. In this study, we aim to assess the efficacy of an ultrasound based anatomy tutorial and the perspectives of a cohort of first year medical students at Queen’s University. Students were recruited, randomized to pre or post-test analysis, and provided with a supplementary lecture on cardiac anatomy utilizing echocardiography studies. In this study, we were unable to demonstrate a difference between understanding of basic cardiac anatomy between groups. However, we were able to report the opinions and perspectives of a small cohort of first year medical students at Queen’s University, illustrating a desire for increased exposure and training towards cardiac POCUS in primary medical education. Further evidence is required to delineate the true value of these experiences.